A Standardized DNA Variant Scoring System for Pathogenicity Assessments in Mendelian Disorders. Issue 1 (29th October 2015) - Karbassi, Izabela; Maston, Glenn A.; Love, Angela; DiVincenzo, Christina; Braastad, Corey D.; Elzinga, Christopher D.; Bright, Alison R.; Previte, Domenic; Zhang, Ke; Rowland, Charles M.; McCarthy, Michele; Lapierre, Jennifer L.; et al.
Abstract : The article by Karbassi et al . describes a standardized DNA variant scoring system that uses multiple lines of evidence, three subclasses of VUS, technical training procedures, and weighted rules‐based scoring to produce reliable and consistent clinical grade variant interpretations. This carefully curated scoring system provides the first roadmap to accurately process complex genetic information in diagnostics. ABSTRACT: We developed a rules‐based scoring system to classify DNA variants into five categories including pathogenic, likely pathogenic, variant of uncertain significance (VUS), likely benign, and benign. Over 16, 500 pathogenicity assessments on 11, 894 variants from 338 genes were analyzed for pathogenicity based on prediction tools, population frequency, co‐occurrence, segregation, and functional studies collected from internal and external sources. Scores were calculated by trained scientists using a quantitative framework that assigned differential weighting to these five types of data. We performed descriptive and comparative statistics on the dataset and tested interobserver concordance among the trained scientists. Private variants defined as variants found within single families ( n = 5, 182), were either VUS (80.5%; n = 4, 169) or likely pathogenic (19.5%; n = 1, 013). The remaining variants ( n = 6, 712) were VUS (38.4%; n = 2, 577) or likely benign/benign (34.7%; n = 2, 327) or likely pathogenic/pathogenic (26.9%, n = 1, 808). Exact agreement between the trained scientists on the final variant score was 98.5% [95% confidence interval (CI) (98.0, 98.9)] with an interobserver consistency of 97% [95% CI (91.5, 99.4)]. Variant scores were stable and showed increasing odds of being in agreement with new data when re‐evaluated periodically. This carefully curated, standardized variant pathogenicity scoring system provides reliable pathogenicity scores for DNA variants encountered in a clinical laboratory setting.